Effect of Moderation of Work Motivation on the Influence of Organizational Culture On Organizational Commitment and Employee Performance - Jufrizen Jufrizen; Mukmin Mukmin; Dinda Nurmala; Hanifah Jasin (International Journal of Business Economics (IJBE), 2021)
This study aims to analyze the influence of organizational culture on employee performance, the influence of organizational culture on organizational commitment, the influence of organizational culture on employee performance through organizational commitment and the role of motivation in moderating the influence of organizational culture on employee performance. This type of research is an associative research using saturated sampling where all members of the population are sampled as many as 85 employees. Data collection techniques are used by questionnaires and data analysis techniques are used by Partial Least Square (SmartPls). Research results show that: (1) the influence of organizational culture on employee performance is positive and significant; (2) the influence of organizational culture on positive and significant organizational commitment; (3) the effect of organizational commitment on positive and significant performance; (4) organizational commitment acts as a mediator on the influence of organizational culture on employee performance; (5) motivation does not act as a moderation on the influence of organizational culture on employee performance.